Parenting in the Context of Male Homosexuality (Research, Society and Development, 2019)
This study aimed to understand homoparentality in contemporary times. Specifically, the specific objectives were: to investigate the adoption criteria for homosexual couples seeking to choose the profile of children in the contemporary world, to understand how the maternal and paternal role is established in male homosexual couples and to analyze the influence on the child development of the new configurations in the context of male homoparentality. A bibliographic research was carried out in the first semester of 2019, in the electronic databases: Scielo, Google Academic, Pepsic, Bireme, CAPES Journal Portal, books and dissertation repositories and theses of universities. In the search for articles, the following descriptors were used: male, adoption, homoparentality, psychoanalysis, childhood. It was found that the contemporary family has a diverse character and not a single model, mainly due to the decline of the paternal function. Homoparentality represents a new family organization that emerged recently, just after the despatologization of homosexual sexuality. Adoption, therefore, is the main form of parenting access by male homosexual couples, and child development is not affected, for a healthy development requires a sufficiently good environment adapted to the child.